Registration of 'Buck' Naked Barley. Issue 1 (26th October 2017) - Meints, Brigid; Corey, Ann; Evans, Chris; Filichkin, Tanya; Fisk, Scott; Helgerson, Laura; Ross, Andrew S.; Hayes, Patrick M.
Abstract : 'Buck' (Reg. No. CV‐363, PI 682744) is a naked (hull‐less), six‐row barley ( Hordeum vulgare L.) cultivar with winter growth habit. The cultivar was released by the Oregon Agricultural Experiment Station in 2015. The name Buck was chosen because the cultivar is naked. Prior to being named, Buck was tested under the experimental designation 09OR‐86. In high‐rainfall environments, it had a yield advantage over the naked check and had an excellent test weight. When grain yield was adjusted for the weight of hulls, Buck was competitive with all checks. Buck is resistant to barley stripe rust and moderately resistant to leaf rust. Buck was developed as a whole‐grain human food barley. However, multi‐use (e.g., food, malting, and feed) is an option. Feeding data are not available. Malting quality data indicate that Buck has higher malt extract than current covered (hulled) malting cultivars. Buck is the first naked winter cultivar to be released with adaptation to the US Pacific Northwest.